Divine Justice and Social Inequality: A Theological Response from Islamic Tradition - Marah, Thomas Sheku (LPPM STAI AL GAZALI BARRU, 2025)
This article examines the fundamental concept of divine justice (‘Adl) through Islamic theological perspectives and its relevance for addressing current social inequalities. Modern societies encounter major economic disparities and systemic social neglect and injustice which demands new theological solutions to these crises. The research uses qualitative literature review methods to analyze classical and modern divine justice interpretations from Al-Ghazālī, Ibn Taymiyyah, Sayyid Qutb, Kamali, Esack, and Ramadan. The Findings shows divine justice functions beyond theoretical abstraction to establish normative guidelines which affect policy decisions, ethical principles, governance systems and human development programs. specifically, it reveals that Islamic theology provides a unified ethical system which addresses poverty reduction alongside gender equality and social justice promotion. The practical implication of this study is that Islamic theology serves as a transformative tool for ethical progress and societal change in modern times through its critical reinterpretation.